FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI MASYARAKAT DALAM PROGRAM BANK SAMPAH DI KELURAHAN BINJAI KECAMATAN MEDAN DENAI KOTA MEDAN TAHUN 2013 - Sarah Patumona Manalu; Indra Chahaya; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Factors related to participation in the trash banks program at the village of Binjai, Medan Denai district, Medan City 2013. Garbage is a wasted or discarded material from sources result of human activity and natural processes that do not have economic value which is now a big problem because of the increased landfill waste by 2-4% per year but it is not matched with support facilities and infrastructure to manage waste maximum. In addition there are a lot of people do not know how to manage and utilize the waste. This study in an analytical study with cross-sectional research design that aims to analyze the factors associated with participation in the garbage bank program at Binjai Village Medan Denai Sub District in 2013 covering factor characteristics, enabling factors and supporting factors in garbage bank program. Population is all people who use and do not utilize the waste bank in Binjai Village Medan Denai Sub District Medan City is 1150 people with a sample of 100 people taken by simple random sampling. Data collected by using questionnaires. Analysis data using chi-square test with a confidence level of 95% (p<0,05), or the fisher exact test. The result showed that the level of community participation in garbage bank program is still very low at 11%. Factors associated with participation in the garbage bank program were occupation, knowledge, availability of trash, and profit of garbage bank. While the factors of education, attitudes, and sorting garbage in the community availability were not related to community participation in the garbage bank program. Conclusion of the research is expected that health workers to socialize to the community particularly through outreach to community leader. Based on these, community leaders will explain the trash bank program in a variety of community activities undertaken in village to motivate the community to be registered as a waste of bank customers. Keywords : Bank Waste, Community Participation, Characteristics, Enabling Supporting